Dynamic changes of pulmonary diffusion capacity in survivors of non-critical COVID-19 during the first six months - Chen, Mu; Liu, Jingwei; Peng, Ping; Jian, Wenhua; Gao, Yi; Fang, Liman; Yu, Yanhui; Zhong, Shuxin; Peng, Hui; Deng, Xilong; Zhou, Yuqi; Du, Sheng; et al. (EClinicalMedicine, 2022)
The dynamic trends of pulmonary function in coronavirus disease 2019 (COVID-19) survivors since discharge have been rarely described. We aimed to describe the changes of lung function and identify risk factors for impaired diffusion capacity. Non-critical COVID-19 patients admitted to the Guangzhou Eighth People's Hospital, China, were enrolled from March to June 2020. Subjects were prospectively followed up with pulmonary function tests at discharge, three and six months after discharge. Eighty-six patients completed diffusion capacity tests at three timepoints. The mean diffusion capacity for carbon monoxide (DLCO)% pred was 79.8% at discharge and significantly improved to 84.9% at Month-3. The transfer coefficient of the lung for carbon monoxide (KCO)% pred significantly increased from 91.7% at discharge to 95.7% at Month-3. Both of them showed no further improvement at Month-6. The change rates of DLCO% pred and KCO% pred were significantly higher in 0–3 months than in 3–6 months. The alveolar ventilation (VA) improved continuously during the follow-ups. At Month-6, impaired DLCO% pred was associated with being female (OR 5.2 [1.7–15.8]; p = 0.004) and peak total lesion score (TLS) of chest CT > 8.5 (OR 6.6 [1.7–26.5]; p = 0.007). DLCO% pred and KCO% pred were worse in females at discharge. And in patients with impaired diffusion capacity, females’ DLCO% pred recovered slower than males. The first three months is the critical recovery period for diffusion capacity. The impaired diffusion capacity was more severe and recovered slower in females than in males. Early pulmonary rehabilitation and individualized interventions for recovery are worthy of further investigations.